Making Native Space: Colonialism, Resistance and Reserves in British Columbia - Lutz, John S. (Labour / Le Travail, 2004)
The article reviews the book, "Making Native Space: Colonialism, Resistance, and Reserves in British Columbia," by Cole Harris.